1997
DOI: 10.1590/s0366-69131997000400005
|View full text |Cite
|
Sign up to set email alerts
|

Alumina para utilização cerâmica, obtida a partir do rejeito de beneficiamento de caulim

Abstract: The kaolin processing for paper covering produces a great volume of residues formed primarily by kaolinite claymineral, here the starting material for the synthesis of ammonium alumen aiming to obtain free sodium alumina with fine grade for ceramic manufacturing. The synthesis process to obtain ammonium alumen consisted of the following procedures: residues calcination and sulphuric leaching of metakaolinite followed by neutralization/ crystallisation of aluminum sulphate solution with ammonium hydroxide conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
7
0
4
Order By: Relevance
“…During the processing steps for purifying raw kaolin, waste is produced and stored in settling ponds which occupy large area. This situation presents a problem due to the impact on the environment 15 . Kaolin waste is unsuitable for use in paper-making industries; however, this material has the potential of being used in other applications, such as: alumina production 15 , refractories 16 , pozzolans 17 and synthesis of zeolitic materials [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…During the processing steps for purifying raw kaolin, waste is produced and stored in settling ponds which occupy large area. This situation presents a problem due to the impact on the environment 15 . Kaolin waste is unsuitable for use in paper-making industries; however, this material has the potential of being used in other applications, such as: alumina production 15 , refractories 16 , pozzolans 17 and synthesis of zeolitic materials [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…A mineração e o beneficiamento do caulim, por sua natureza, envolvem atividades que alteram as condições ambientais provocando impactos ao meio físico e biótico [3] fazendo com que este minério, apesar de sua importância em várias indústrias, esteja associado a um grande passivo ambiental [4]. O processo de beneficiamento do caulim destinado para carga e cobertura de papel gera dois tipos de rejeitos: um composto por partículas grosseiras (principalmente quartzo sob a forma de areia), que são repostas no próprio local da lavra, e outro que é armazenado em volumosas lagoas de sedimentação [5]. Pesquisas com esse rejeito demonstram uma grande viabilidade para o mesmo ser utilizado como matéria-prima em diversos segmentos industriais [5,6], como por exemplo, na síntese para obtenção de zeólitas [7][8][9].…”
Section: Introductionunclassified
“…O processo de beneficiamento do caulim destinado para carga e cobertura de papel gera dois tipos de rejeitos: um composto por partículas grosseiras (principalmente quartzo sob a forma de areia), que são repostas no próprio local da lavra, e outro que é armazenado em volumosas lagoas de sedimentação [5]. Pesquisas com esse rejeito demonstram uma grande viabilidade para o mesmo ser utilizado como matéria-prima em diversos segmentos industriais [5,6], como por exemplo, na síntese para obtenção de zeólitas [7][8][9].…”
Section: Introductionunclassified
“…In order to take advantage of the kaolin residue in the many sectors involved in the ceramic industry, several studies have been developed in recent decades. Among them can mention: Flores & Neves (1997), concluded that the methodology of alumina production through the use of tailings from the processing of kaolin is technically feasible, according to the parameters for the roasting, leaching and neutralization / crystallization adopted in his research.  Miranda et al, (2000) studied the use of kaolin waste from industry benefited, with a view to the application as ceramic raw materials.…”
Section: Potential Of Kaolin Residue As Secondary Raw Materialsmentioning
confidence: 99%